Mysticism and Treatment: Tools of Healing and Case Study Practices of Spiritual Alternative Medicine in Boarding Schools - Fathin Fauhatun Fauhatun (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The modern era is known as the era of progress in various aspects of human life, should be able to bring prosperity, build happiness together towards an ethical, moral life and create peace. However, what happens is very different, humans experience a lot of hardships, mental anxiety, tension and emotional stress. This study aims to reintroduce the values of Sufism and can be applied in everyday life. This research is a library research, so the pattern used is reflective-inductive deductive. By using a psychological approach. Discussing the relationship between Sufism and medicine, where previously Sufism was understood to tend to distance itself from social activities but it turns out that Sufism is not the case in modern times Sufism plays an important role in overcoming complaints faced by humans, in practice Sufism can be used as a means of treatment and methods used in carrying out Treatment using tasawuf can be done to overcome psychological problems, by cleansing the mind and re-practicing religious values in order to achieve the pleasure of Allah, to apply these treatment Islamic boarding schools are a forum for helping the application of treatment through Sufism.